Construction de récits et encodage de procès par des bilingues russes/français - Tatiana Aleksandrova (Corela)
This study is devoted to an analysis of near-native speakers’ productions. We presuppose that not only the First Language (L1) influences the productions in the Second Language (L2), but the L2 can also affect the productions in the L1. The oral discourse in French by Russian/French near-native speakers is influenced by the L1 in the area of back-ground composition, and linguistic choices. The productions in the L1, differ from that of Russian monolinguals in the area of event representation and in the organisation of elements in the utterance. The cases of linguistic trasfer are visible in the both languages.